Capacity Building Opportunities for Climate Risk Management in Senegal - Diop, Mbaye; Grossi, Amanda; Hansen, James; Konte, Oumar; Lecuyer, Anais; Tall, Thierno; Trzaska, Sylwia; Whitbread, Anthony M.; Worou, Nadine (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Capacity development is an important part of the Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA) strategy to make climate services and climate-smart agriculture more accessible to millions of smallholder farmers across Africa. To inform planning towards AICCRA-Senegal capacity development objectives, this paper reviews capacity gaps that currently limit the farm-level benefits of climate services in Senegal, and presents opportunities for competency-based curriculum and training to strengthen capacity to incorporate climate knowledge into agricultural decision making from farm to national scales. Although Senegal has a strong foundation for agricultural climate services, current delivery strategies leave a gap in farmers’ capacity to use probabilistic information at a climate variability time scale. A gender plan that incorporates the channels that rural women use can help ensure that agricultural climate services reduce existing gender-based inequalities. Short-term training for the network of organizations (ANCAR, NGOs, producer organizations) that provide extension and advisory services provides a promising opportunity to improve the use of climate services at the farm level. Other promising targets for building capacity to utilise climate information include university agriculture programs and local level multi-stakeholder engagement platforms. Ongoing curriculum development activities in Ethiopia offer useful lessons, and an agricultural extension short course curriculum that offers a potential starting point for efforts in Senegal.